L’évolution des usages des prépositions en, dans, dedans entre le XVIe et le XXe siècle : approche distributionnelle sur corpus outillé - Denis Vigier (Discours)
We present a diachronic study of the evolution of the collocational profile of the French prepositions en, dans, and dedans, between the 16th century and the 20th century. The historical corpus used, fully annotated (morphosyntax and lemmas), was created during the Franco-German “Presto Program 2013-2017” (http://www.agence-nationale-recherche.fr/?Projet=ANR-12-FRAL-0010). We show that the oft-cited analyses of Gougenheim (1970a and b) on the semantic evolution of en and dans during this period are only partially verified. Our study reveals that: i) en has continued up to modern French to maintain a close link with localization; ii) from the 18th century on, dans took on a highly specific nominal pattern with an abstract polarity, that led it to share with en many of the latter’s favourite collocations; iii) in particular, dans took over the spatial and material value of the old dedans.